Annualized Returns of Venture-Backed Public Companies Categorized by Stage of Financing: An Empirical Investigation of IPOS in the Last Three Decades - Yochanan Shachmurove (Journal of Entrepreneurial Finance, 2001)
Although the national media has given increased attention to the venture capital process, misconceptions continue to proliferate. One often hears about the incredible capital gains of IPO share prices. This paper refutes the myth that investors demand very high rates of return to compensate for the risks involved in financing ventures. The paper investigates actual performance of 3,063 Initial Public Offerings of companies that were backed by venture capital from 1968 until 1998 stratified by current actively and inactively traded companies and by stages of financing. The main findings are that annualized returns are different for current actively and inactively traded firms and for many of the stages of financing but that they are much lower than the ones reported by the media and the venture capital literature.
Keywords: C12; D81; D92; E22; G12; G24; G3; M13; M21; O16; O3; 650; Venture Capital; Venture-Backed Companies; Initial Public Offering; IPO; MBO; Seed Financing; Mezzanine